Passive and Active Measurement 11th International Conference, PAM 2010, Zurich, Switzerland, April 7-9, 2010, Proceedings - Krishnamurthy, Arvind; Plattner, Bernhard (Computer Communication Networks and Telecommunications, 2010)
The 2010 edition of the Passive and Active Measurement Conference was the 11th of a series of successful events. Since 2000, the Passive and Active M- surement (PAM) conference has provided a forum for presenting and discussing innovative and early work in the area of Internet measurements. PAM has a tradition of being a workshop-like conference with lively discussion and active participation from all attendees. This event focuses on research and practical applications of network measurement and analysis techniques. This year's c- ference was held at ETH Zurich, Switzerland. PAM 2010 attracted 79 submissions. Each paper was carefully reviewed by at leastthreemembersoftheTechnicalProgramCommittee.Thereviewingprocess ledtotheacceptanceof23papers.Thepaperswerearrangedinninesessionsc- ering the following areas: routing, transport protocols, mobile devices, topology, measurement infrastructure, characterizing network usage, analysis techniques, tra?c analysis, and the Web. We are very grateful to Endace Ltd. (New Zealand), Cisco Systems Inc. (USA), armasuisse (Switzerland) and the COST Action TMA whose sponsoring allowedustokeepregistrationcostslowandto o?erseveraltravelgrantsto PhD students. We are also grateful to ETH Zurich for sponsoring PAM as a host.